TEKNOLOGI PETANI MUDA PADA USAHATANI CABAI MERAH DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG - Nugie Arisandi; Said Masduki; Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2022)
This study aims to know the application of technology carried out by young farmers in the red chili farming business in Bocek Village and to know the income of young farmers' farming in Bocek Village. The sampling method in this study is the census sampling method. The ampel was used by as many as 40 young red chili farmers aged 20 to 35 years who came from five farmer groups in Bocek Village. The analysis used in this study is an analysis of the application of technology, namely by using the formula of the percentage of the level of application and analysis of farming efforts. The results showed that the level of application of pink chili farming technology for young farmers in Karangploso District, Malang Regency, was included in the high category where the number of observation values was 1,937 with an average observation value of 77.48 and an average percentage of 96.85%. The total income earned by young farmers is Rp. 41,361,246 with an R/C ratio of 1.94, the farming of young farmers is worth cultivating.